Analisis Resiko dan Perilaku Petani Bawang Putih di Kabupaten Bantul - Ari Astuti; Sri Widodo; Masyhuri Masyhuri (Agro Ekonomi, 1994)
Garlic farming is new commodity in Bantul regency, showed that have highly risk with low average production and high fluctuation in price.